Validitas Dan Praktikalitas E-Modul Fisika Terintegrasi Bencana Covid-19 Berbasis Model Problem Based Learning (PBL) Untuk Meningkatkan Kesiapsiagaan Peserta Didik Pada Kurikulum Merdeka - Putri Nurhaliza; Ahmad Fauzi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Based on the observation conducted by the researcher in MAN 1 Kerinci shown that the student’s learning outcome still have not reached the KKM. One of the reasons is the teachers have not been able to compose learning materials in accordance with the demands of the curriculum. Learning model by teachers have not been able to guide the students in learning. Therefore, it is necessary to develop learning materials by PBL. This study was aimed to develop learning materials the from e-modul by PBL integrated covid-19 to straight motion subjects with valid, practical, and effective. Methodology of this study was research and development. The development model used was 4-D model consist of define, design, development, and disseminate. In the define phase, it was done curriculum, student, and material analysis. In the design phase, it was done by designing learning materials the from e-modul. In the development phase, it was done test of validity, practicality, and the effectivity of e-modul. Then in the disseminate phase, it was done test of practicalities, and effectiveness. The data about test of validity was obtained trough the validation sheet of e-modul. Data about test of practicality was obtained trough observation sheet of lesson plan accomplishment and the questionnaire responses of teachers and learners. Data about test of effectivity was obtained trough an assessment of knowledge, attitudes, and skills of learners. Then, the data about increase student’s creative thinking skill was obtained trough comparison between the ready attitude analysis of early and late. The analysis of material was obtained straight motion. In the design phase, it was obtained initial draft of e-modul that consist in the development phase, it was obtained e-modul which has valid criteria (0,86), practically criteria (94%).